2019
DOI: 10.3390/ijerph16101752
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation in the Concentration of Inhalable Particulate Matter (PM10) in Uganda

Abstract: Long-term particulate matter (PM10) measurements were conducted during the period January 2016 to September 2017 at three sites in Uganda (Mbarara, Kyebando, and Rubindi) representing a wide range of urbanization. Spatial, temporal and diurnal variations are assessed in this paper. Particulate matter (PM10) samples were collected for 24-h periods on PTFE filters using a calibrated pump and analyzed gravimetrically to determine the average density. Particulate levels were monitored simultaneously using a light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…high temperature, low wind-speed and absence of precipitation) may produce stagnant conditions that substantially amplify local anthropogenic emissions [ 56 ]. The daily PM 2.5 cycle of bimodal pattern with peaks in the mornings and evenings, provides further support for the influence of rush hour traffic, biomass combustion as well as pollution build-up due to temperature inversion and variations in meteorological conditions between day and nighttime hours and seasons [ 23 , 57 ]. It is likely that the observed improvements in PM 2.5 pollution, especially in high-density neighborhoods that also tended to have high-biomass use, was due to gradual reductions in biomass use.…”
Section: Discussionmentioning
confidence: 96%
“…high temperature, low wind-speed and absence of precipitation) may produce stagnant conditions that substantially amplify local anthropogenic emissions [ 56 ]. The daily PM 2.5 cycle of bimodal pattern with peaks in the mornings and evenings, provides further support for the influence of rush hour traffic, biomass combustion as well as pollution build-up due to temperature inversion and variations in meteorological conditions between day and nighttime hours and seasons [ 23 , 57 ]. It is likely that the observed improvements in PM 2.5 pollution, especially in high-density neighborhoods that also tended to have high-biomass use, was due to gradual reductions in biomass use.…”
Section: Discussionmentioning
confidence: 96%
“…The review identified reports on disinfection byproducts, such as trihalomethanes (THMs), in drinking water supplies (122). In addition, particulate matter, including fine and coarse particulates (PM2.5 and PM10), was also a subject of investigation in air quality studies (98,124,125).…”
Section: Resultsmentioning
confidence: 99%
“…Airborne particles and gases can carry pollutants such as persistent organic pollutants (POPs) and microplastics over long distances, leading to their deposition in ecosystems, including water bodies and soils. Study conducted by (124,125), 152.6 µg/m 3 of PM2.5 and 208 µg/m 3 of PM10 were measured in air samples around the districts of Kampala, Jinja and Mbarara in Uganda. This review identified that a few studies investigating airborne emerging pollutants have so far been done.…”
Section: Ambient Air As a Transport Medium For Emerging Pollutantsmentioning
confidence: 99%
“…PM 10 data were collected from three sites with a real-time monitor (TSI SidePak AM510) using an impactor with a 10 µm cut-off, as described in [21]. The sites were in Mbarara, Rubindi, and Kyebando.…”
Section: Pm 10 Datamentioning
confidence: 99%